PENGARUH BUDAYA ORGANISASI SEKOLAH DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA DI SMA NEGERI DI KABUPATEN PATI - Sri Saptono Yuni Ismoyo, 11.52.20.0012 (Students Journal of Economic and Management, 2013)
This study aimed to examine the influence of organizational culture and leadership of school principals on teacher performance with the mediation of job satisfaction in the high schools in Pati regency. The research was conducted for teachers in high schools in Pati many as 150 people, using a data collection techniques populations. Statistical technique used is the component matrix validity, reliability test by Cronbach alpha, multiple regression analysis, t test and the test with the adjusted r Â² r square. The results showed that job satisfaction variables proved to mediate the influence of organizational culture and leadership of school principals on teacher performance. Organizational culture and leadership of school principals have a positive and significant effect on performance. Variable organizational culture school, the principals leadership and job satisfaction affects the performance of 80.1%. The remaining 19.9% ââis influenced by other variables not included in the study. Keywords: Organizational Culture School, Principal Leadership, Job Satisfaction and Teacher Performance